Assessment and prognostic significance of the epidermal growth factor receptor vIII mutation in glioblastoma patients treated with concurrent and adjuvant temozolomide radiochemotherapy. Issue 10 (19th November 2013) - Weller, Michael; Kaulich, Kerstin; Hentschel, Bettina; Felsberg, Joerg; Gramatzki, Dorothee; Pietsch, Torsten; Simon, Matthias; Westphal, Manfred; Schackert, Gabriele; Tonn, Joerg C.; von, Andreas; Davis, Thomas; et al.
<x xml:space="preserve">Abstract</x> The epidermal growth factor receptor vIII mutant (EGFRvIII) is found in ∼50% of all EGFR‐amplified glioblastomas and constitutes a tumor‐specific therapeutic target. To assess molecular testing approaches and the prognostic role of EGFRvIII in patients treated according to current standards of care, we compared different EGFRvIII detection methods and correlated EGFRvIII status with outcome in a prospective patient cohort of the German Glioma Network. In total, 184 newly diagnosed glioblastoma patients were investigated for EGFR amplification and for expression of EGFR and EGFRvIII by immunohistochemistry. Further, the EGFRvIII status was additionally studied by multiplex ligation‐dependent probe amplification (MLPA) analysis and reverse transcription‐PCR (RT‐PCR). Immunohistochemistry demonstrated EGFRvIII in 34 of 184 patients (18%). RT‐PCR or MLPA analysis detected four additional EGFRvIII‐positive patients. Overall, RT‐PCR and immunohistochemistry were more sensitive for EGFRvIII detection than MLPA. EGFRvIII status was not associated with progression‐free and overall survival. EGFRvIII also had no prognostic significance in the subgroup of patients who were free from progression after concomitant radiochemotherapy and thus would be eligible for the ongoing ACT IV EGFRvIII vaccination trial. Age, extent of resection and O6‐methylguanine DNA methyltransferase (MGMT) promoter methylation status appeared to be less prognostic in EGFRvIII‐positive patients. Thus, EGFRvIII positivity is not a major negative prognostic factor in glioblastoma patients treated according to current standards of care. Data from phase II EGFRvIII‐targeted vaccination trials compare favorably with the present contemporary results, supporting the further exploration of EGVRvIII vaccination in newly diagnosed glioblastoma.